1967
DOI: 10.1021/es60011a006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical aspects of the photooxidation of the propylene-nitrogen oxide system

Abstract: The photooxidation of part-per-million concentrations of propylene in the presence of similar concentrations of nitric oxide has been investigated. The product yields were measured over a wide range of reactant concentrations and reactant ratios. Series of experiments were carried out with varying light intensities, with both static and dynamic flow conditions. The products measured by colorimetric, gas chromatographic, and various monitoring instruments included nitrogen dioxide, oxidant (ozone and other oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
57
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 16 publications
8
57
0
Order By: Relevance
“…In the photooxidation of the propylene-nitrogen oxide system, Altshuller et a/. 5 reported good nitrogen balances up to the time when NO2 reached a maximum. After that time, the nitrogen balance depended on the initial NO* concentration.…”
mentioning
confidence: 99%
“…In the photooxidation of the propylene-nitrogen oxide system, Altshuller et a/. 5 reported good nitrogen balances up to the time when NO2 reached a maximum. After that time, the nitrogen balance depended on the initial NO* concentration.…”
mentioning
confidence: 99%
“…The first manifestation of the problem occurred the Los Angeles area and included accelerated deterioration of rubber products, damage to vegetation, and eye irritation (6)(7)(8). While the problem is severest in the southwest part of the U.S, high levels of oxidants are known to occur in every major urban center in this country and, through short and long range transport, oxidant spreads to non-urban areas and even to other countries (9).…”
Section: Introduction I-a Historymentioning
confidence: 99%
“…Extensive research has uneqivocally identified several components of photochemical oxidant mixtures (7,(10)(11). Thus, photochemical oxidants are known to consist mainly of ozone (03) radicals.…”
Section: Introduction I-a Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxyacetyl nitrate yields increase curvilinearly with irradiation of increasing concentrations of olefins or aldehydes 6 -8 but show more complex behavior with maximum yield similar but not identical to that of ozone as nitrogen oxides concentrations vary in irradiated olefin-nitrogen oxide 6 and alkylbenzene-nitrogen oxide mixtures. 8 The concentration and distribution of products causing eye irritation formed from the photochemical reactions of various classes of hydrocarbons with nitrogen oxide are such that the eye irritation potentials are in the order: alkylbenzenes > olefins > paraffins > acetylene.…”
mentioning
confidence: 95%